Gender Stereotypes of women managers in Indian organizations - Sujoya Basu (INDIAN INSTITUTE OF MANAGEMENT CALCUTTA WORKING PAPER SERIES WPS No. 580/ January 2006, 2006)
The lack of studies on gender stereotypes of women managers in India despite the dismally low number of women in the top tiers of Indian organizations prompted this study. Managerial gender stereotypes held by both sexes in Indian organizations are explored in this study. 105 men managers and 93 women managers separately rated one of three managerial sets (men managers, women managers and successful middle managers) of the modified Schein Descriptive Index (1973). While results for the male sample differed from previous studies for worse, results for the female sample were positive. Women managers showed significantly increased associations between middlemanagerial success and women managers, as compared to the western context about two decades ago. Twenty managerial gender stereotypes relevant to the Indian context were identified.